2009
DOI: 10.1097/ta.0b013e31818e90ed
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Malignant Syndrome in Traumatic Brain Injury Patients Treated With Haloperidol

Abstract: Development of NMS in TBI patients treated with haloperidol should be a concern for clinicians since these patients may be at greater risk for this adverse event; especially if the patient is receiving haloperidol at high doses parenterally. Future studies are needed to evaluate the incidence and increased risk of adverse events in patients sustaining a TBI and receiving haloperidol especially since haloperidol is being used more frequently in the critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…[4] The diagnosis in this case was further complicated by the fact that the patient had received a single dose of haloperidol. Previous reports indicate that NMS in traumatic brain injury patients is typically triggered by at least 10 mg of haloperidol, with most patients receiving ≥30 mg.[7] It is important for the intensivist to have NMS on the differential diagnosis for all patients who may be withdrawing from dopaminergic agonists, which must be considered in trauma patients for whom a complete history is not available. [8] Moreover, it must be remembered that neuroleptics have side effects even at home doses, and their use during a period of cocaine withdrawal can lead to an exacerbation of withdrawal symptoms, NMS, or even death.…”
Section: Discussionmentioning
confidence: 99%
“…[4] The diagnosis in this case was further complicated by the fact that the patient had received a single dose of haloperidol. Previous reports indicate that NMS in traumatic brain injury patients is typically triggered by at least 10 mg of haloperidol, with most patients receiving ≥30 mg.[7] It is important for the intensivist to have NMS on the differential diagnosis for all patients who may be withdrawing from dopaminergic agonists, which must be considered in trauma patients for whom a complete history is not available. [8] Moreover, it must be remembered that neuroleptics have side effects even at home doses, and their use during a period of cocaine withdrawal can lead to an exacerbation of withdrawal symptoms, NMS, or even death.…”
Section: Discussionmentioning
confidence: 99%
“…[2511] Younger patients are at higher risk for the development of NMS, it is twice more common in male, the reported incidence of NMS with use of haloperidol is ranging from 0.02 to 12.2%. [4]…”
Section: Discussionmentioning
confidence: 99%
“…None of the cases reported NMS in head injury patients had mortality. [4] Higher levels of CPK in these patients indicate the severity of the disease and correlate with the higher mortality. Dentrolene and bromocriptin therapy will reduce the morbidity and mortality in NMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that patients with traumatic brain injury should be monitored closely, especially if they are receiving haloperidol parenterally at high doses. It is important to note that haloperidol may have negative effects on cognition and function, making it an unattractive medication in this patient population (46). The development of heme pigment-associated renal failure from rhabdomyolysis is an important risk factor for mortality (30).…”
Section: Nmsmentioning
confidence: 99%